Scaling for Agricultural Impacts: Together and Responsibly - Dror, Iddo; MacMillan, Susan; Schneidt, Agnes; Schut, Marc; Kangethe, Edwin; Buono, Nicoletta (CGIAR System Organization, 2024)
In October 2023, CGIAR's Second Annual Week on the Science and Practice of Scaling Agrifood Innovations took place, attracting around 100 experts to the campus of the International Livestock Research Institute (ILRI) in Nairobi, Kenya. This significant event, organized by the CGIAR Research Initiative on Diversification in East and Southern Africa (“Ukama Ustawi”), the CGIAR Portfolio Performance Unit (PPU), and ILRI, facilitated a deep dive into advancing the science and practice of scaling agricultural innovations to transform Africa’s agrifood systems. Participants included representatives from 8 CGIAR centers and 24 external organizations, collaborating in a series of plenary sessions, panel discussions, and interactive workshops. This 4-page summary distills the key outcomes and insights from the event, capturing the collaborative spirit and strategic discussions aimed at scaling agricultural impact responsibly and effectively across the continent.